Analisis Waktu Baku Pembuatan Produk Gasket di PT. Nichias Rockwool Indonesia - Widi Widiarti; Dene Herwanto (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2021)
Nichias Rockwool Indonesia is a pioneer in heat protection materials and technology protection in various industrial sectors. PT. Nichias Rockwool Indonesia has several main products which are divided into three parts, namely rockwool, sealing gasket, and autoparts. The production process involves machines such as forming, winding, marking and so on. In order to increase production capacity, PT. Nichias Rockwool Indonesia uses a target completion time for a product. Therefore, it is necessary to calculate the standard time in the completion of the gasket assembly process. Process standard time in a company allows a uniform period of time used to complete production within a company. The measurement of working time to be carried out in this study uses the stopwatch time study method. This method is done by measuring time by observing and recording work operation times. This time data will then be calculated standard time. The number of research data is 150 data taken from selected trained operators. Factors of adjustment and allowances (allowance) using the Westinghouse method. The result of this research is that the cycle time is 21.67 seconds, the normal time is 23.62 seconds, and the standard time is 28.34 seconds. Production capacity before the standard time was only 553 gaskets per day, after calculating the standard time it increased to 889 gaskets per day or 54.97%. Keywords: production capacity, stopwatch time study, standart time